FINANCIAL, TECHNICAL AND STRATEGIC ANALYSIS : METHODS AND TECHNIQUES FOR ANALYZING BUSINESS ENVIRONMENT AND COMPETITION FOR OPTION TRADING - -, Damini; Čabla, Adam, 1985-; Habarta, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
In nutshell, the thesis's aim is to find out the tools which today's investors use to find the ultimate or golden decision of BUY, HOLD, or Sell. Apart from exploring different analytical tools thesis's aim is to conclude that is any of the tools is effective in really predicting the direction of the market. One thing which everyone wants to know is the end result of the Options Trading. Options Trading is a very complicated field, where no matter how many no. of parameters or indicators are taken into consideration it can pull the direction and can take even a highly knowledgeable to surprise. Although centuries after centuries, decades after decades still we try to analyze it to make condition under our favor & predict the market. In this paper, we have tried an investigative approach to land up a conclusion after analyzing a Czech Republic-based company listed on Prague Stock Exchange. For analysis, we will use the age-old tool of fundamental/financial analysis which will involve various financial ratios taking into consideration the sentiment of the market & the company’s nature and investment. We will further try to do a technical analysis of the company which will involve use of python programming & will involve the use of machine learning specifically regression & classification (Supervised learning). Technical Analysis is the new age tool that evolved in the last decade due to the advent of programming tools in the field of data engineering which has enabled the industry to do analysis on large data sources which were not imaginable before by anyone.
Technical Analysis has its own requirement and works on certain indicators to get started its analysis so that we have to look out for as is Prague Stock Exchange is capable of providing such high rich data for the analysis? In this paper by implementing both the fundamental & technical analysis, we will try to figure the comparison between both the analysis & reach a particular conclusion in two parts-(i)First what are the issues the trader of the Czech republic is facing while investing and simultaneously finding out how data-rich is Prague Stock Exchange & (ii)Secondly -will in future be really able to predict the market correctly which the Machine learning strategies claim & have huge hype to their name.
Vedoucí práce: Adam Čabla
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses